The Effect of Pressure on Magnetic Properties of Prussian Blue Analogues - Maria Zentkova; Marian Mihalik (Crystals, 2019)
We present the review of pressure effect on the crystal structure and magnetic properties of Cr(CN)6-based Prussian blue analogues (PBs). The lattice volume of the fcc crystal structure space group Fm <semantics> <mover accent="true"> 3 ¯ </mover> </semantics> m in the Mn-Cr-CN-PBs linearly decreases for p ≤ 1.7 GPa, the change of lattice size levels off at 3.2 GPa, and above 4.2 GPa an amorphous-like structure appears. The crystal structure recovers after removal of pressure as high as 4.5 GPa. The effect of pressure on magnetic properties follows the non-monotonous pressure dependence of the crystal lattice. The amorphous like structure is accompanied with reduction of the Curie temperature (TC) to zero and a corresponding collapse of the ferrimagnetic moment at 10 GPa. The cell volume of Ni-Cr-CN-PBs decreases linearly and is isotropic in the range of 0⁻3.1 GPa. The Raman spectra can indicate a weak linkage isomerisation induced by pressure. The Curie temperature in Mn2+-CrIII-PBs and Cr2+-CrIII-PBs with dominant antiferromagnetic super-exchange interaction increases with pressure in comparison with decrease of TC in Ni2+-CrIII-PBs and Co2+-CrIII-PBs ferromagnets. TC increases with increasing pressure for ferrimagnetic systems due to the strengthening of magnetic interaction because pressure, which enlarges the monoelectronic overlap integral S and energy gap ∆ between the mixed molecular orbitals. The reduction of bonding angles between magnetic ions connected by the CN group leads to a small decrease of magnetic coupling. Such a reduction can be expected on both compounds with ferromagnetic and ferrimagnetic ordering. In the second case this effect is masked by the increase of coupling caused by the enlarged overlap between magnetic orbitals. In the case of mixed ferro⁻ferromagnetic systems, pressure affects μ(T) by a different method in Mn2+⁻N≡C⁻CrIII subsystem and CrIII⁻C≡N⁻Ni2+ subsystem, and as a consequence Tcomp decreases when the pressure is applied. The pressure changes magnetization processes in both systems, but we expect that spontaneous magnetization is not affected in Mn2+-CrIII-PBs, Ni2+-CrIII-PBs, and Co2+-CrIII-PBs. Pressure-induced magnetic hardening is attributed to a change in magneto-crystalline anisotropy induced by pressure. The applied pressure reduces saturated magnetization of Cr2+-CrIII-PBs. The applied pressure p = 0.84 GPa induces high spin⁻low spin transition of cca 4.5% of high spin Cr2+. The pressure effect on magnetic properties of PBs nano powders and core⁻shell heterostructures follows tendencies known from bulk parent PBs.